OPTIMALISASI MEDIA PEMBELAJARAN YANG INTERAKTIF SEBAGAI UPAYA MENINGKATKAN MOTIVASI ANAK DALAM MINAT BACA AL-QUR'AN DI TPQ KASYIFATUL ULUM BANDENGAN - Ani Ariyanti; Ana Rahmawati (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to analyze the function of interactive learning media in increasing children's enthusiasm in reading the Qur'an at TPQ Kasyifatul Ulum Bandengan. The research method applied is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research findings indicate that the use of interactive learning media, although only limited to basic tools such as whiteboards and hijaiyah letter cards, can increase children's enthusiasm for learning. Children's interest in reading is influenced by fun teacher methods and parental support at home. However, there are still challenges such as boredom in learning and the negative impacts of using gadgets. Therefore, consistent and innovative optimization of interactive media is needed to build an effective, fun learning process that is in accordance with the characteristics of digital generation children.